Pengaruh Ideologi Etis Terhadap Penilaian Etis - Rahma Nakhiral Marta; Vanica Serly (Universitas Negeri Padang, 2023)
The purpose of this study was to examine the influence of ethical ideology on ethical judgments. This research contributes to the existing literature on student ethical judgment, particularly in the context of a developing country such as Indonesia. There are 193 of accounting students Faculty of Economics Universitas Negeri Padang who have taken/are currently taking courses Ethics on Accounting Profession. This study shows that idealism doesn’t have positive effect on Ethical Judgment, while relativism shows negative results on ethical judgment.